2001
DOI: 10.1111/j.1530-0277.2001.tb02156.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Vulnerability of Embryonic Cell Populations to Ethanol‐Induced Apoptosis: Implications for Alcohol‐Related Birth Defects and Neurodevelopmental Disorder

Abstract: The results of this study revealed developmental stage-specific cell populations of the developing brain and craniofacial region that are vulnerable to ethanol-induced apoptosis and provide new insight relative to the genesis of alcohol-related birth defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
179
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(199 citation statements)
references
References 90 publications
(56 reference statements)
18
179
0
2
Order By: Relevance
“…We have previously demonstrated that apoptosis (cell death) can be visualized in 8-9 days old mouse embryos, rat fetal limbs, and other tissues using a fluorescent dye (LysoTracker Red, LT), which stains lysosomes and acidic regions of cells/tissues (16)(17)(18)(19)(20)(21)(22)(23). The current study extends our previous work to visualize apoptosis within follicles of a whole ovary (17).…”
supporting
confidence: 66%
See 3 more Smart Citations
“…We have previously demonstrated that apoptosis (cell death) can be visualized in 8-9 days old mouse embryos, rat fetal limbs, and other tissues using a fluorescent dye (LysoTracker Red, LT), which stains lysosomes and acidic regions of cells/tissues (16)(17)(18)(19)(20)(21)(22)(23). The current study extends our previous work to visualize apoptosis within follicles of a whole ovary (17).…”
supporting
confidence: 66%
“…From previous studies on embryos, the appearance of LT in tissue is strongly suggestive of apoptosis (16)(17)(18)(19)(20)(21)(22)(23). The LT has a fluorescence peak at 610 nm (Leica SP1), while the AIF has a fluorescence peak around 471 nm with UV or cyan GFP excitation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast, ethanol can cause death of post-mitotic neurons (Miller, 1995;Jacobs and Miller, 2001;Mooney and Miller, 2001a;Heaton et al, 2003;Mooney et al, 2006). Embryos exposed to ethanol during gastrulation display increased expression of markers associated with cell death (Dunty et al, 2001;2002). Such labeling is most apparent in the cranial neural crest, which may underlie the craniofacial changes, and the rostral hindbrain, i.e., rhombomeres 1-3, inclusive.…”
Section: Mechanisms Of Ethanol Toxicitymentioning
confidence: 99%